2012
DOI: 10.1080/08959420.2012.630905
|View full text |Cite
|
Sign up to set email alerts
|

Are Baby Boomers Who Care for Their Older Parents Planning for Their Own Future Long-Term Care Needs?

Abstract: A rapidly expanding number of baby boomers provide care to aging parents. This study examines associations between caregiver status and outcomes related to awareness and anticipation of future long-term care (LTC) needs using 2007 Connecticut Long-Term Care Needs Assessment survey data. Baby boomers who were adult child caregivers (n = 353) vs. baby boomers who were not (n = 1242) were more likely to anticipate some future LTC needs and to have considered certain financing strategies. Although baby boomer adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In the past decade, researchers have begun examining LTC needs and planning among baby boomers. A number of studies found that both current older adults and baby boomers have a strong preference for staying in their own homes . Researchers have also found that boomers were also no different from the older adults when it came to their degree of financial planning to pay for LTC and their expectations for requiring LTC services in the future .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the past decade, researchers have begun examining LTC needs and planning among baby boomers. A number of studies found that both current older adults and baby boomers have a strong preference for staying in their own homes . Researchers have also found that boomers were also no different from the older adults when it came to their degree of financial planning to pay for LTC and their expectations for requiring LTC services in the future .…”
Section: Introductionmentioning
confidence: 99%
“…Third, personal experience with LTC, both receiving or providing such care, might activate a planning mindset. As existing literature pointed out, the absence of urgency might postpone any proactive LTC planning . Finally, individuals need to engage in advance financial planning in order to be able to receive adequate or preferred LTC services.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CDC has recently reported that nearly one third (30.5%) of deaths associated with injury include a diagnosis of TBI and there are an estimated 5.3 million U.S. residents living with TBI-related disabilities [1]. Economic costs resulting from TBI were estimated at $76.5 billion for 2010, including $11.5 billion for direct medical costs and $64.8 billion for indirect costs (e.g., lost wages, lost productivity, and nonmedical expenditures) [2, 3]. TBI has been described as the “signature” injury of veterans from the conflicts in Iraq and Afghanistan, where repetitive and multiple combat injures are common [4].…”
Section: Introductionmentioning
confidence: 99%